Stochastic processes dominate community assembly of ectomycorrhizal fungi associated with Picea crassifolia in the Helan Mountains, China - Zhang, Xuan; Wang, Yonglong; Xu, Ying; Babalola, Busayo Joshua; Xiang, Simin; Ma, Jianjun; Su, Yun; Fan, Yongjun (Frontiers in Microbiology, 2023)
Understanding the underlying mechanisms of microbial community assembly is a fundamental topic in microbial ecology. As an integral part of soil organisms, ectomycorrhizal (EM) fungi play vital roles in ecosystems. Picea crassifolia is an important pine species in the Helan Mountains in Inner Mongolia, China with a high ecological and economic values. However, studies of EM fungal diversity and mechanisms underlying community assembly on this pine species are limited. In this study, we investigated EM fungal communities associated with P. crassifolia from 45 root samples across three sites in the Helan Mountains using Illumina Miseq sequencing of the fungal rDNA ITS2 region. A total of 166 EM fungal OTUs belonging to 24 lineages were identified, of which Sebacina, and Tomentella-Thelephora were the most dominant lineages. Ordination analysis revealed that EM fungal communities were significantly different among the three sites. Site/fungus preference analysis showed that some abundant EM fungal OTUs preferred to specific sites. Ecological process analysis implied that dispersal limitation and ecological drift in stochastic processes dominantly determined community assembly of EM fungi. Our study indicates that the P. crassifolia harbors a high EM fungal diversity and highlights the important role of stochastic process in driving community assembly of mutualistic fungi associated with a single plant species in a semi-arid forest in northwest China.